2015
DOI: 10.1245/s10434-015-4484-5
|View full text |Cite
|
Sign up to set email alerts
|

The Supporting Role of 18FDG-PET in Patients with Neuroendocrine Tumors

Abstract: There has been a marked, unexplained increasing incidence of neuroendocrine tumors (NETs) over the past few decades. This may be due to a combination of different factors, such as changes in the environment with new exposures to injurious agents or an increased awareness of these neoplasms, but perhaps most of all, improvements in and utilization of body imaging. It has been estimated that as many as 72 million computed tomographic (CT) scans are done per year in the United States, a threefold increase since 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Therefore, 18 FDG-PET/CT may have value for staging, prognosis, and selecting NET patients who might benefit from medical versus surgical therapy, but the utility of these scans appears to be limited to patients with higher grade tumors. 130 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, 18 FDG-PET/CT may have value for staging, prognosis, and selecting NET patients who might benefit from medical versus surgical therapy, but the utility of these scans appears to be limited to patients with higher grade tumors. 130 …”
Section: Resultsmentioning
confidence: 99%
“…18 F-FDG PET/CT imaging has also been compared with 68 Ga-DOTA peptide imaging in several studies, which have shown it to have variable sensitivity in detecting NETs (15)(16)(17)(18)(19)(20)(21)(22). However, the presence of increased glucose in NETs highlights an increased propensity for invasion and metastasis, and 18 F-FDG PET/CT accordingly has higher sensitivity in delineating disease extent, especially in aggressive and high-grade tumors (23). Detection of a higher number of lesions is nevertheless not always followed by a change in disease stage and, most importantly, does not always affect the therapeutic approach.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed a significant correlation between dual-tracer PET/CT imaging and tumor differentiation. 18 F-FDG performs well for the evaluation and management of high-grade NENs (poorly differentiated and aggressive) [30], but has limitations for the determination of metastatic lesions in well-differentiated NENs, because 18 F-FDG PET/CT is positively correlated with the degree of tumor malignancy and is less sensitive in well-differentiated NETs. There is thus a significant positive correlation between the SUVmax of BMs detected by 18 F-FDG and Ki-67 index [31].…”
Section: Discussionmentioning
confidence: 99%